Climatic niche shift in the amphitropical disjunct grass Trichloris crinita - Quiroga, Raul Emiliano (2018)
Plant species disjunctions have attracted the interest of ecologists for decades. We investigated Trichloris crinita, a native C4 perennial grass with disjunct distribution between subtropical regions of North and South America, testing the hypothesis that the species has a similar realized climatic niche in both subcontinents. The climatic niche of T. crinita in North and South America was characterized and compared using presence records and five uncorrelated bioclimatic variables selected according to their ecological importance for the species. We used reciprocal modeling to make geographic projections of the realized niche within each subcontinent. Niche overlap between T. crinita distributions in North and South America was intermediate for the individual climatic variables and the multivariate space. In all cases the test of equivalence between climates inhabited by T. crinita indicated that the realized niche of the species differ significantly between subcontinents. Also, the similarity test showed that in the majority of cases the realized niche in both subcontinents was significantly different than that expected by chance. T. crinita occupied a greater diversity of environments in South than in North America, while in the latter its distribution was displaced to drier and warmer environments. The modeled geographic distribution using the actual occurrences of the species in North America did not accurately predict the distribution in South America, and vice versa. Together, these results led us to reject the hypothesis of similar niche of T. crinita in both subcontinents. This information may be useful to manage restoration efforts by presenting the suitable areas and climates for the species, and suggesting that translocation of individuals between subcontinents could only be recommended with caution because introduced genotypes can be potentially maladaptive, and could colonize sites actually not occupied by the species within each subcontinent.